Keselarasan Budaya Hukum dan Prinsip Perbankan Syariah pada Masyarakat Multireligius di Kepulauan Kei, Maluku - Moh Yamin Rumra; Syah Awaluddin; Evi Savitry Gani (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
The Kei Islands community adheres to the Larvul Ngabal customary law, which governs various aspects of social and economic life. The philosophy of Ain Ni Ain, emphasizing brotherhood and justice, serves as the foundation for Yelim, a mutual aid system for managing social funds within the community. Additionally, the Kei people have implemented cultural accounting practices in recording and managing communal funds, which align with the principles of transparency and accountability in Islamic banking. However, the acceptance of Islamic banking among the Kei people remains a challenge, particularly within a multireligious community. This study is a sociological legal research (Socio-Legal Research) that employs a descriptive qualitative method with an ethnomethodological approach, involving interviews with customary leaders, religious figures, business actors, and the general public. The findings indicate that the values of Ain Ni Ain and Yelim align with Islamic banking principles, particularly in terms of social justice and financial transparency. Moreover, cultural accounting practices in communal fund management reflect an accountability mechanism similar to Islamic accounting standards. Thus, integrating Kei’s indigenous financial system with Islamic banking offers an innovative approach to enhancing financial inclusion in multireligious societies.